Sensor integration in rubber gaskets for structural health monitoring made by compression molding. (December 2015) - Schotzko, Timo; Reuter, Mark; Lang, Walter
Abstract: This research work shows the integration process and characterization of a miniaturized strain gauge sensor in rubber O-rings for structural health monitoring (SHM). Strain gauges have been successfully embedded during compression molding, which is a commonly used fabrication method of rubber components. The sensor signal is correlated with the contact pressure of the gasket that abates over time due to aging processes. This can be exploited for lifetime prediction. Embedding sensors into rubber applying compression molding is a novel method that allows the integration into non-liquid elastomers. The strain gauge resistance correlates linearly to the contact pressure. An artificial aging test exhibits an exponential decrease in the resistance caused by the relaxation processes during the accelerated aging of the elastomer at 70 °C for 72 h. Uniaxial tensile testing with dumbbell specimens reveals the influence of the integrated sensors. It is demonstrated that the influence heavily depends on the sensor size.